2011
DOI: 10.3390/md9122622
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Cytotoxic Effects of 13-Acetoxysarcocrassolide from the Soft Coral Sarcophyton crassocaule on Bladder Cancer Cells

Abstract: Active compounds from natural products have been widely studied. The anti-tumor effects of 13-acetoxysarcocrassolide isolated from Formosan soft coral Sarcophyton crassocaule on bladder cancer cells were examined in this study. An MTT assay showed that 13-acetoxysarcocrassolide was cytotoxic to bladder female transitional cancer (BFTC) cells. We determined that the BFTC cells underwent cell death through apoptosis by flow cytometry. Due to the highly-migratory nature of the BFTC cells, the ability of 13-acetox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 79 publications
2
35
0
1
Order By: Relevance
“…Cytoskeleton rearrangement altered the activity of colon cancer cells, which was associated with MYL12B (17). Su et al (18) observed that the overexpression of hnRNP F influenced the development of colon tumors and interfered with normal apoptosis and energy metabolism of bladder cells, which could result in bladder cancer. DES, TPM3, TPM2 and vimentin are important in maintaining the stability of the cytoskeleton, and changes in vimentin expression were associated with liver cancer metastasis and recurrence (19).…”
Section: Discussionmentioning
confidence: 99%
“…Cytoskeleton rearrangement altered the activity of colon cancer cells, which was associated with MYL12B (17). Su et al (18) observed that the overexpression of hnRNP F influenced the development of colon tumors and interfered with normal apoptosis and energy metabolism of bladder cells, which could result in bladder cancer. DES, TPM3, TPM2 and vimentin are important in maintaining the stability of the cytoskeleton, and changes in vimentin expression were associated with liver cancer metastasis and recurrence (19).…”
Section: Discussionmentioning
confidence: 99%
“…2,9,24 The concentrations of protein were determined by bicinchoninic acid assay according to the manufacturer's instructions. In all, 10% sodium dodecyl sulfate-polyacrylamide gel electrophoresis was used to run and separate the protein samples.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…It has been found that several natural compounds from soft corals have cytotoxic and apoptosis-inducing effects against melanoma cells, hepatocellular carcinoma cells, and bladder cancer cells in our previous studies. 2,9,10 Heteronemin (HET) is a known sesterterpenoid extracted from the sponge Hippospongia sp. This natural marine compound was found to inhibit the enzyme protein farnesyltransferase and reduce the viability of leukemia cells, colon cancer cells, and breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…memiliki kemampuan menghalangi pertumbuhan sedikitnya satu dari tujuh isolat pembentuk bio-filum. S. crassocaule diketahui memiliki potensi sitotoksik terhadap sel kanker kandung kemih (Su et al, 2011). Sarcophyton juga dinyatakan mengandung diterpenoid laut yang dapat dimanfaatkan sebagai agen anti-inflamasi (Gonzalez et al, 2015).…”
Section: Pendahuluanunclassified